2020
DOI: 10.1111/1746-692x.12280
|View full text |Cite
|
Sign up to set email alerts
|

How do Stakeholders Perceive the Sustainability and Resilience of EU Farming Systems?

Abstract: Summary An increasing variety of stresses and shocks provides challenges and opportunities for EU farming systems. This article presents findings of a participatory assessment on the sustainability and resilience of eleven EU farming systems, to inform the design of adequate and relevant strategies and policies. According to stakeholders that participated in workshops, the main functions of farming systems are related to food production, economic viability and maintenance of natural resources. Performance of f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 5 publications
0
27
0
Order By: Relevance
“…Most studies reported quantitative data, and very few used qualitative scores and/or semi-quantitative data (6.5%). Future research may benefit from the use of qualitative or semi-quantitative scores to assess more implicit and abstract concepts, such as cultural services (Boerema et al 2017), and to assess more dimensions of sustainability and resilience at once (Reidsma et al, 2020). The use of models to obtain estimations as a final outcome was also limited to a reduced number of studies (14%).…”
Section: Methods and General Characteristics Of The Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies reported quantitative data, and very few used qualitative scores and/or semi-quantitative data (6.5%). Future research may benefit from the use of qualitative or semi-quantitative scores to assess more implicit and abstract concepts, such as cultural services (Boerema et al 2017), and to assess more dimensions of sustainability and resilience at once (Reidsma et al, 2020). The use of models to obtain estimations as a final outcome was also limited to a reduced number of studies (14%).…”
Section: Methods and General Characteristics Of The Studiesmentioning
confidence: 99%
“…Three main components of resilience can be highlighted (Meuwissen et al 2019): robustness, the capacity of systems to resist stresses and remain with similar performance and characteristics; adaptability, the capacity of systems to rearrange their composition of inputs, production, marketing and risk management in response to stresses; and transformability, which entails significant changes in system structure and feedback mechanisms in response to severe disturbances that make the current system no longer feasible (Meuwissen et al 2019). It is worth noting that resilience is closely related to the other sustainability dimensions, as it refers to system stability over time, in terms of ecosystem services provision, biodiversity conservation, input requirements and socio-economic factors (Reidsma et al 2020). Although the concept of resilience is intrinsically linked to a temporal dimension, some authors propose the use of static measures, such as diversity, as a proxy for resilience (Mijatović et al 2013;Andrade and Zapata 2019).…”
Section: Other Categoriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite these limitations, the resilience attributes of the SURE-Farm frameworkdiversity, openness, adequate feedbacks, system reserves and modularitywere generally confirmed as relevant predictors of resilience, although the precise materialization of these attributes differs across time, place and scale. During the SURE-Farm project, these attributes were specified for farming systems, and the most important ones in the recent past were: reasonable profitability, social self-organization, infrastructure for innovation, production coupled with local and natural capital, and response diversity (Chapter 17; Paas et al, 2019;Reidsma, Meuwissen, et al, 2020). However, while these attributes are perceived to contribute to robustness and adaptability, the contribution to transformability was questioned by stakeholders, with the exception of infrastructure for innovation, if it is implemented with a vision.…”
Section: Seven Lessons Learned On the Resilience Frameworkmentioning
confidence: 99%
“…The enhancement of resilience attributes such as "coupled with the local and natural capital" and "ecologically self-regulated" in future systems showed the importance of integrating ecosystem services into farm management. Our assessment suggested that economic problems hinder the promotion of sustainability and resilience (Reidsma et al, 2020b). Although farmers are exposed to both economic and social challenges, they assigned a high importance to the function "Economic viability" and a low importance to social functions ("Attractiveness of the area" and "Quality of life"), revealing that economic issues are perceived as most urgent.…”
Section: Improving the Sustainability And Resilience Of European Farm...mentioning
confidence: 87%